The Effect of Using Tiktok Shop Live Streaming, Price Discounts and Free Shipping on Skintific Skincare Purchase Decisions - Sin, Virda Mei; Susanto, Annie (Daengku: Journal of Humanities and Social Sciences Innovation, 2025)
This study investigates the influence of TikTok Shop live streaming, discount promotions, and free shipping offers on the purchasing decisions of Skintific skincare products among university students. Given the increasing use of social media platforms for e-commerce, particularly TikTok, live streaming has emerged as an interactive marketing strategy. A quantitative research approach was used, with survey data collected from university students, who were chosen due to their familiarity with technology and diverse skincare needs. Multiple regression analysis was employed to determine the impact of each independent variable on purchasing decisions. The findings indicate that live streaming and free shipping significantly influence consumers' decisions to purchase Skintific skincare, while discount promotions do not have a significant effect. The results suggest that interactive and engaging live streaming content, as well as free shipping, are effective in driving purchases, whereas discounts may not always lead to increased consumer interest. These findings provide practical insights for marketers to prioritize engaging live streaming and strategic free shipping offers while reconsidering the role of discounts